CARDIOTROPHIN-1 REVIEW - Stejskal, David; Ruzicka, Viktor (Biomedical papers, 2008)
Background: Cardiotrophin-1 is newly discovered chemokin with a lot of functions. Aim of our work was to describe most important of them.Methods: systematically scan of available scientific resources.Results: Cardiotrophin-1 stimulates the proliferation of cardiomyocytes. Cardiotrophin-1 expression and plasma values are elevated in individuals with heart failure and have high diagnostic efficacy for the heart failure. Plasma values are also an independent prognostic factor. Preliminary findings suggest that the determination of plasma cardiotrophin-1 may be useful for the follow-up of hypertensive heart disease in routine clinical practice. Cardiotrophin-1 also plays an important cardioprotective effect on myocardial damage, is a potent regulator of signaling in adipocytes in vitro and in vivo and potentiates the elevation the acute-phase proteins. Cardiotrophin-1 may play also an important protective role in other organ systems (such as hematopoietic, neuronal, developmental).Conclusion: Cardiotrophin is a newly discovered chemokin with a lot of system effects and is stable in system circulation hence permitting its development in the routine clinical investigation.
Keywords: Acute Coronary Syndromes/Metabolic Syndrome/Cardiovascular Diseases/ Cancers/Laboratory markers/Cardiotrophin-1/ELISA